Proctoclysis for rehydration in children – A scoping review and a pilot survey among medical doctors. (December 2022) - Henrik, Szőke; Janka, Szőke; David, Martin; Vagedes, Jan; Ágnes, Kiss; Zoltán, Kovács; Adam, Dobrylovsky; Odilia, Mussler; Andrea, Kisbenedek; Zsófia, Verzár; Rebeka, Szőke
Abstract: Although proctoclysis (enema) is a historically proven, safe and cost-effective rehydration method that needs little training for users and can effectively replace intravenous hydration in different care settings, it is an uncommon choice for hydration in children with fever and is often missing in official guidelines. To evaluate the usefulness of proctoclysis, this study provides a scoping review of the existing literature. The matched literature was labelled in 5 categories, identifying 6 indication fields that are emphasized in the literature on rectal rehydration. The analysis showed that proctoclysis is mostly used in the context of diagnostic procedures, constipation or in the treatment of a gastrointestinal disease. It is also described as a quick, safe and cost-effective intervention for fluid replacement in emergency, critical care or resource-scarce settings. There are also socio-cultural variations in its use Additionally, we performed a survey on attitudes and experience of medical doctors towards proctoclysis based on a semi-structured questionnaire. In the survey, we analysed the experience of 35 medical doctors from 8 countries. Although we found a general acceptance of enema as beneficial in both hospitalized patients and in home care, doctors expressed the need for more experience with enema and the need for more education materials in order to effectively perform the procedure. Based on our findings, we suggest that further research is necessary examining the attitude towards proctoclysis among parents, nurses and doctors. Enema can have a considerable clinical advantage during home care for gastroenteritis or other infectious diseases with fever to prevent insufficient oral fluid intake resulting in a negative fluid balance. Risks and safety issues are rare and should be considered. However, due to its low level of social acceptability in order to reduce refusal rate, more education is necessary for both medical providers and parents. Highlights: Proctoclysis is a historically proven safe, low traumatic, cost-effective rehydration method for small children. It can be considered for home care of gastroenteritis or other infectious diseases resulting in a negative fluid balance. It can be lifesaving in resource-scarce settings or where hospitalization is associated with incalculable risks and trauma. It needs some expertise/experience, e.g. some advice on volume and frequency and can effectively replace IV hydration. Due to its low level of social acceptability, efforts should be made to educate about its advantages.